Essential Norm of Difference of Composition Operators from Weighted Bergman Spaces to Bloch-Type Spaces - Ram Krishan; Mehak Sharma; Ajay K. Sharma (Journal of Function Spaces)
We compute upper and lower bounds for essential norm of difference of composition operators acting from weighted Bergman spaces to Bloch-type spaces.